Representasi Identitas Muslimah Modern “Jilbab Traveler” dalam Novel Karya Asma Nadia - Rani Dwi Putri (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2020)
Following the fall of the New Order era, which encouraged media development and openness, Islam was positioned as a dominant identity in public spaces. Asma Nadia is one of the actors who is become one part of those phenomena. Her works in novels, films and soap operas have succeeded in combining modern elements with Islamic symbols and values. The theme of Jilbab traveler is one example. Applying text analysis focusing on three works of Asma Nadia’s novels, namely The Jilbab Traveler; Assalamualaikum Beijing; Jilbab Traveler: Love Sparks in Korea, this article reveals that Asma Nadia illustrates